Cochrane Corner: Interventions to Improve Hearing Aid Use in Adult Auditory Rehabilitation. (December 2014) - Burton, Martin J.; Adams, Meredith E.; Rosenfeld, Richard M.
The "Cochrane Corner" is a section in the journal that highlights systematic reviews relevant to otolaryngology–head and neck surgery, with invited commentary to aid clinical decision making. This installment features the Cochrane review "Interventions to Improve Hearing Aid Use in Adult Auditory Rehabilitation, " which identified 32 randomized controlled trials and concluded that there is low-quality evidence to support using self-management support and complex interventions (support plus delivery system design) in adult auditory rehabilitation.